Early inflammatory players in cutaneous fibrosis - Raker, Verena; Haub, Jessica; Stojanovic, Ana; Cerwenka, Adelheid; Schuppan, Detlef; Steinbrink, Kerstin (Journal of dermatological science, 2017)
Systemic sclerosis (SSc) is one of the most complex systemic autoimmune diseases with multi-organ involvement and heterogeneous clinical manifestations. The exact etiology of SSc is still unknown. However, identified target structures are components of endothelial cells, the innate/adaptive immune systems and fibroblasts, resulting in the hallmarks of the disease in form of inflammation/autoimmunity, vasculopathy and fibrosis of the skin and internal organs. There has been a large body of evidence that the adaptive immune system with autoreactive T and B cells producing autoantibodies plays a central role in the pathogenesis of SSc but the role of earlier pathogenic processes involving the innate immune system, is far from being understood. There is strong evidence that a dysregulation of innate lymphoid cells and myeloid cells critically contributes to early pathogenic events in SSc. As disruption of vascular homeostasis and a fibroproliferative vasculopathy are hallmarks of early SSc, intravascular processes including platelet activation and interaction with neutrophils and monocytes, may even be upstream of innate immune deviation. Therefore, further studies of the dysregulated innate immune system may provide insights into novel and potentially curative treatments of SSc. In this review, we highlight the most relevant findings regarding the involvement of innate immune cells during the early stage of cutaneous fibrosis in SSc, with emphasis on the role of neutrophils, myeloid cells and innate lymphoid/NK cells in the pathogenesis of SSc and their potential as therapeutic targets for this difficult-to-treat autoimmune disease.